Multiliteracies Pedagogy and Language Learning Teaching Spanish to Heritage Speakers (Springer International Publishing, 2018)
This book is the first volume to be devoted to the examination of the application of the Multiliteracies pedagogical framework to the teaching of Spanish to heritage language learners in higher education institutions in the United States. The Hispanic population is a growing minority, and the presence of heritage speakers can be observed in second language Spanish classes in all levels of education, which presents unique challenges for practitioners. This collection focuses on differing populations of learners in educational settings in a variety of geographical areas, such as Arizona, California, Maryland, Massachusetts, Ohio, Tennessee, and Texas. The studies included in the volume offer invaluable data and methodological insights into the instructional advantages of multiliteracies pedagogies in heritage language classrooms, and they will appeal to Spanish practitioners and researchers as well as those interested in the education and practice of heritage languages. Gabriela C. Zapata is Associate Professor and Director of Lower Division Spanish Instruction in the Department of Hispanic Studies at Texas A&M University, USA. Her research focuses on second and heritage language acquisition and pedagogy, bilingualism and teacher education, and she has published widely on these topics. Manel Lacorte is Associate Professor of Spanish Applied Linguistics, Director of the Spanish Language Program and Director of the MA Program in Hispanic Applied Linguistics at the University of Maryland, USA. His research interests include second language and heritage language pedagogy and teacher education, second language classroom interaction and context(s) and applied linguistics. He has published several edited volumes and a number of articles in leading journals. .